-6t+2+3t=-7

Simple and best practice solution for -6t+2+3t=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6t+2+3t=-7 equation:


t in (-oo:+oo)

3*t-6*t+2 = -7 // + 7

3*t-6*t+2+7 = 0

9-3*t = 0 // - 9

-3*t = -9 // : -3

t = -9/(-3)

t = 3

t = 3

See similar equations:

| -4d+6+d=-18 | | m+4+2m=10 | | 7+4a+7a=95 | | 10+x-6x=10 | | -88=3k+6k+2 | | 10=6a-3a-5 | | 50=4d+2d-10 | | 2d+1+2d=-27 | | 3t+7+6t=70 | | -7+5m+7m=29 | | 7t-2+2t=88 | | -5n-8+2n=-8 | | -1-4x+5x=0 | | 2d+4+d=25 | | 64=7b+2b-8 | | 2b-6+3b=24 | | 8+3b+2b=-2 | | 2d+1+4d=37 | | 4-n-6n=11 | | -5k+6-6k=-49 | | 5-3a+a=-7 | | 4+7a-4a=10 | | -13=2x-3x-1 | | 4=-6b+3b+1 | | 8+6k-2k=4 | | -w-10-2w=-37 | | -5-3n-6n=-14 | | 7a+6-6a=9 | | 8=3m-2m+5 | | 6m+1+2m=41 | | 1-b+6b=1 | | 5w+1-4w=1 |

Equations solver categories